(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background; Celiac disease is the inflammatory entropy caused by hypersensitivity to gluten, which occurs in susceptible individuals. Some studies have suggested a link between celiac disease and epilepsy in children; Gluten-related disorders (GRDs) represent a spectrum of diverse clinical manifestations triggered by the ingestion of gluten. Aim and objectives; the aim of this review was to establish the prevalence of epilepsy in patients with coeliac disease (CD) or gluten sensitivity (GS) and vice versa and to characterise the phenomenology of the epileptic syndromes that these patients present with, Subjects and methods: A systematic computer-based literature search was conducted on the PubMed database. Information regarding prevalence, demographics and epilepsy phenomenology was extracted by keywords as epilepsy; celiac disease; prevalence; children, Conclusion; The data indicate that the prevalence of CD or GS is higher amongst particular epileptic presentations including in childhood partial epilepsy with occipital paroxysms, in adult patients with fixation off sensitivity (FOS) and in those with temporal lobe epilepsy (TLE) with hippocampal sclerosis. A particularly interesting presentation of epilepsy in the context of gluten-related disorders is a syndrome of coeliac disease, epilepsy and cerebral calcification (CEC syndrome) which is frequently described in the literature, greater attention is required to the possible coexistence of celiac disease in epileptic children. Children with various idiopathic types of epilepsy, and especially children with persistent seizures, should be screened for silent celiac disease in order to prevent nonreversible complications,